AN ANALYSIS OF RHETORICAL DEVICES IN THE WIZARD LIZ’S MOTIVATIONAL SPEECHES ON YOUTUBE - Mawaddah, Aliyya; Yusmalinda, Yusmalinda; Nazara, Waozisokhi (LINGUA LITERA : journal of english linguistics and literature, 2025)
This study aims to analyze the rhetorical devices used by The Wizard Liz in her motivational YouTube videos. This study focuses on identifying and classifying both schemes and tropes found in the video by using theory from Corbett and Connors (1999). The method used is qualitative descriptive analysis, with three selected videos as the primary data sources. The data source is from the videos that were uploaded in 2024, with titles such as “Understand how valuable you are”, “How to manifest a new life”, and “Watch this to believe in yourself”. The video contains 57 rhetorical devices. The results show that The Wizard Liz frequently used rhetorical devices such as anaphora and rhetorical questions. The findings support Corbett and Connors’ theory that such devices are powerful tools in persuasive communication. In conclusion, The Wizard Liz uses rhetorical techniques in her motivational content to create emotionally engaging and impactful messages for her viewers.